965 Accuracy of emergency (999) telephone triage for predicting adverse outcomes in suspected COVID-19: an observational cohort study. Issue 3 (21st February 2022) - Marincowitz, Carl; Bath, Peter; Hasan, Madina; Stone, Tony; Campbell, Richard; Pilberry, Richard; Turner, Janette; Thomas, Benjamin; Goodacre, Steve
Abstract : Aims/Objectives/Background: In the first wave of the pandemic some ambulance services received three times their usual number of 999 calls. The increase was mostly due to calls from patients with respiratory symptoms. Call handlers must rapidly decide whether patients need an emergency face-to-face assessment or could access non-emergency services. We assess accuracy of emergency telephone triage in identifying patients with suspected COVID-19 infection who need an ambulance response and identify factors which affect triage accuracy. Methods/Design: An observational cohort study of adults who contacted 999 emergency telephone services provided by Yorkshire Ambulance Service between the 18 th March 2020 and 29 th June 2020 with symptoms indicating possible COVID-19 infection was completed. Callers were linked to ONS death registrations and routine health care data collected by NHS Digital. The accuracy of triage outcome (ambulance dispatch versus telephone advice) was assessed for death or organ support 30 days from first contact. Multi-variable logistic regression was used to identify factors associated with risk of false negative or false positive triage. Results/Conclusions: Of the 12, 655 callers, 11.1% experienced the primary outcomes. An ambulance was dispatched to 84.2% of callers. The decision to dispatch an ambulance achieved 95% sensitivity (95% CI: 93.7 to 96.1%) and 17.2% specificity (95% 16.5% to 17.9%) for adverse outcomes. Where an ambulance was not dispatched, patients had a 3.5% (2.8 to 4.4%) of subsequent deterioration. Of patients that received an ambulance only 57% were subsequently conveyed to hospital. Multivariable logistic regression modelling found false negative assessment was associated with younger age and female sex and false positive assessment was associated with malignancy, immunosuppression, respiratory and cardiovascular comorbidities. Emergency telephone triage of patients with suspected COVID-19 achieved a high sensitivity to serious adverse outcomes. Further research is required to identify ways specificity of triage could be improved to reduce unnecessary ambulance dispatch.